Content Analysis of the Book “Teaching Methods of Arabic Language” Based on the Quality indicators of Educational Books - Sajad Esmaili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main purpose of this research is to investigate the weaknesses and strengths of the book entitled "Teaching Methods of Arabic Language" by Ali Aḥmad Madkour based on the quality indicators of educational books. The research method is descriptive and the focus is on the content analysis. The main research tool is the "check list" of content analysis, the main components of which are the quality indicators of educational books. The results of this research demonstrated that this book lacks some general quality indicators such as proper page layout, introduction, purpose explanation, summary of chapters, results and suggestions, and some content quality indicators such as explaining theoretical and practical principles, accuracy in expressing opinions, and referring .However, some of the indicators, such as clarity and coordination between the main and the subtitle, the coordination between the chapters, the critical approach in expressing the issues, the accuracy of the use of specialized terminology and methodology are the most important points of the book